Measures of experimental precision in common bean and soybean genotype trials - Filho, Alberto Cargnelutti; Storck, Lindolfo; Ribeiro, Nerinéia Dalfollo (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to evaluate the appropriateness of statistics heritability, determination coefficient, F-test value for genotype, Fasoulas index of differentiation and selective accuracy, as measures of the degree of experimental precision in a set of common bean (Phaseolus vulgaris) and soybean (Glycine max) genotype competition trials. Grain yield data from 72 genotype competition trials of common bean and 216 of soybean, carried out in Rio Grande do Sul state, Brazil, were used. Based on 12 statistics estimated for each trial, correlation, path and cluster analyses were done, and the trial frequency in each class of experimental precision was calculated. The statistics selective accuracy, heritability, coefficient of determination and F-test value for genotype are more adequate than the coefficient of variation and the significant minimum difference among cultivars by Tukey's test, expressed in percentage of the mean, to evaluate the experimental precision of common bean and soybean yield trials. According to those statistics, 88.89% of the common bean experiments and 75% of the soybean experiments showed a high or very high degree of precision, and 2.78% and 10.19% of the experiments of common bean and soybean, respectively, could be discarded due to insufficient experimental precision.